Enhanced mitochondrial inhibition by 3, 4‐dihydroxyphenyl‐acetaldehyde (DOPAL)‐oligomerized α‐synuclein. Issue 12 (16th August 2019) - Sarafian, Theodore A.; Yacoub, Amneh; Kunz, Anastasia; Aranki, Burkan; Serobyan, Grigor; Cohn, Whitaker; Whitelegge, Julian P.; Watson, Joseph B.
Abstract: Oligomeric forms of α‐synuclein are believed to cause mitochondrial injury, which may contribute to neurotoxicity in Parkinson's disease (PD). Here oligomers of α‐synuclein were prepared using the dopamine metabolite, DOPAL (3, 4‐dihydroxyphenyl‐acetaldehyde), in the presence of guanidinium hydrochloride. Electron microscopy, mass spectrometry, and Western blotting studies revealed enhanced and stable oligomerization with DOPAL compared with dopamine or CuCl2 /H2 O2 . Using isolated mouse brain mitochondria, DOPAL‐oligomerized α‐synuclein (DOS) significantly inhibited oxygen consumption rates compared with untreated, control‐fibrillated, and dopamine‐fibrillated synuclein, or with monomeric α‐synuclein. Inhibition was greater in the presence of malate plus pyruvate than with succinate, suggesting the involvement of mitochondrial complex I. Mitochondrial membrane potential studies using fluorescent probes, JC‐1, and Safranin O also detected enhanced inhibition by DOS compared with the other aggregated forms of α‐synuclein. Testing a small customized chemical library, four compounds were identified that rescued membrane potential from DOS injury. While diverse in chemical structure and mechanism, each compound has been reported to interact with mitochondrial complex I. Western blotting studies revealed that none of the four compounds disrupted the oligomeric banding pattern of DOS, suggesting their protection involved direct mitochondrial interaction. The remaining set of chemicals also did not disrupt oligomeric banding, attesting to the high structural stability of this α‐synuclein proteoform. DOPAL and α‐synuclein are both found in dopaminergic neurons, where their levels are elevated in PD and in animal models exposed to chemical toxicants, including agricultural pesticides. The current study provides further evidence of α‐synuclein‐induced mitochondrial injury and a likely role in PD neuropathology. Abstract : Oligomeric forms of α‐synuclein are believed to cause neurotoxicity in Parkinson's disease (PD) in part by causing mitochondrial injury. The dopamine metabolite, 3, 4‐dihydroxyphenyl‐acetaldehyde (DOPAL), oligomerized α‐synuclein (DOS), which inhibited (−) brain mitochondrial functions including oxygen consumption rate (OCR) and membrane potential. Four unrelated small molecules rescued (+) DOS‐induced mitochondrial inhibition.